1989
DOI: 10.1038/bjc.1989.191
|View full text |Cite
|
Sign up to set email alerts
|

Modification by vasoactive drugs of tumour destruction by photodynamic therapy with haematoporphyrin derivative

Abstract: Since the vascular endothelium is a primary site of damage after photodynamic therapy (PDT), it seemed likely that drugs which affect the vasculature may modify the outcome of PDT. Noradrenaline, propranolol, hydralazine and phenoxybenzamine inhibited photodynamic damage to tumours if these drugs were administered concurrently with HPD, 2 h before irradiation. This inhibition was associated with reduced uptake of HPD into tumours. There was no inhibition if irradiation was delayed until 24 h after administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Therefore, many attempts have been made to enhance the absolute uptake of HpD or PII in tumours. Cowled & Forbes [3] demonstrated that the administration of verapamil, a calcium-channel-blocking agent, simultaneously with HpD, to mice bearing Lewis lung carcinoma increased the uptake of HpD in the tumour. Adriamycin and methotrexate, two chemotherapeutic drugs, were found to increase the accumulation of HpD in Lewis lung tumours in vivo [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many attempts have been made to enhance the absolute uptake of HpD or PII in tumours. Cowled & Forbes [3] demonstrated that the administration of verapamil, a calcium-channel-blocking agent, simultaneously with HpD, to mice bearing Lewis lung carcinoma increased the uptake of HpD in the tumour. Adriamycin and methotrexate, two chemotherapeutic drugs, were found to increase the accumulation of HpD in Lewis lung tumours in vivo [4].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that elimination of the PDT vascular response was observed after pretreatment with the cyclo-oxygenase inhibitors indomajor effect on both tumor and nontumor vascu- methacin and acetyl salicylic acid tends to confirm this hypothesis. Cowled and Forbes [5] demonstrated that many vasoactive drugs could be used to modify the PDT response, and the addition of calcium channel blockers seemed to inhibit tumor regrowth after PDT. There is also evidence that the vascular changes that occur post-PDT are both light-dose and drug-dose related [61.…”
Section: Introduction Words: Window Chamber Vascular Response Tissumentioning
confidence: 99%
“…Continued evidence that vascular injury is a primary in vivo site of PDT damage has led to an investigation of vasoactive drugs in combination with PDT by Cowled and Forbes (1989). Noradrenaline, propranonol, hydralazine and phenoxybenzamine inhibited tumoricidal effects of PDT by reducing porphyrin uptake in tumors.…”
Section: In Vivo Pharmacology and Toxicology Of Photosensitizersmentioning
confidence: 99%